High-thermal-conductivity composite perovskite catalyst and preparation method thereof

By using high-thermal hexagonal boron nitride material and metal additive La in the catalyst, a high-thermal composite perovskite catalyst is formed, which solves the stability and cost of the catalyst under high temperature conditions, and achieves higher catalytic performance and Longer service life.

CN119140142APending Publication Date: 2024-12-17JIANGSU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411278109.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing catalysts are prone to sintering, agglomeration and loss under high temperature conditions, and precious metal catalysts are costly and have low durability, which limits their industrial applications.

Method used

High thermal conductivity hexagonal boron nitride material is used as a support and metal additive La is introduced to form a highly thermally conductive composite perovskite catalyst, which improves the high temperature stability and aging resistance of the catalyst through the modification process.

Benefits of technology

It significantly improves the high temperature stability, durability and carbon deposit performance of the catalyst, extends the service life, and shows excellent catalytic performance in reactions such as thermal oxidation of low concentration methane, reducing the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140142A_ABST
    Figure CN119140142A_ABST
Patent Text Reader

Abstract

The invention discloses a high-thermal-conductivity composite perovskite catalyst and a preparation method thereof, and belongs to the technical field of waste gas treatment catalysts. The chemical general formula of the high-thermal-conductivity composite perovskite catalyst is MFC / M-N, MFC is catalytic active center perovskite, and the mass fraction of MFC is 60-80 wt.%; m is a catalyst carrier, selects a BN high-thermal-conductivity carrier, and accounts for 9-30 wt.% of the mass of the catalyst; n is a metal auxiliary agent La and accounts for 1-30 wt.% of the mass of the catalyst. According to the high-thermal-conductivity composite perovskite catalyst and the preparation method thereof, the high-thermal-conductivity material is adopted as the carrier, the metal additive is introduced, reaction heat is rapidly and uniformly dispersed by means of the high-thermal-conductivity carrier, and thermal management of the catalyst is improved; and the metal additive inhibits high-temperature sintering agglomeration by increasing the defects of the catalyst. The combination of the two significantly improves the high-temperature catalytic stability, aging resistance and carbon deposition performance of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of waste gas treatment catalysts, and in particular to a high thermal conductivity composite perovskite catalyst and a preparation method thereof. Background Art

[0002] At present, the global energy consumption structure is dominated by the three major fossil energy sources of oil, coal and natural gas, accounting for more than 70%, while clean energy such as electricity, wind power, nuclear energy and biomass energy are in the development stage and are not mature in terms of technology, system and market. Therefore, the energy structure dominated by traditional resources will be difficult to change for a long time in the future. Human production activities inevitably emit a large amount of pollutants, such as carbon dioxide, methane, sulfide and nitrogen oxides. Among them, as a greenhouse gas, the greenhouse effect caused by CH4 is much higher than that of CO2, and its ability to absorb heat in the atmosphere is 23 times that of CO2. The concentration of this part of methane is generally far below its combustion limit, and it is difficult to recycle or directly burn it.

[0003] Catalytic combustion technology is considered to be a convenient and efficient solution for utilizing low-concentration methane. This technology can achieve the ignition of methane at a lower temperature, which has a positive effect on improving the combustion process, reducing the reaction temperature, promoting complete combustion and inhibiting the generation of toxic and harmful substances. At present, catalytic combustion technology has been applied in many aspects of industrial production and daily life. In order to achieve efficient utilization of methane, the development of high-performance catalysts is particularly important. Generally, precious metals such as Pt, Pd and Rh are used as the main commercial catalysts. Such catalysts are conducive to the breaking of methane CH bonds due to their unique empty d electron orbits and rich coordination. However, the high cost and low high-temperature durability of such precious metal catalysts limit their long-term application.

[0004] In recent years, some transition metal (Fe, Co, Al, Mn, Cu) oxides have been widely studied in the field of catalytic combustion due to their excellent catalytic activity and environmental friendliness. Composite metal oxides composed of these metal elements show advantages such as higher catalytic activity, wider temperature application window and better high temperature stability, and are therefore considered to be potential substitutes for precious metals in methane catalytic reactions. Among them, perovskite materials not only have ideal catalytic activity, but also have advantages in catalytic selectivity, electrochemical properties and economic cost, making them more attractive in low-concentration methane high-temperature catalysis. In addition, conventional catalyst carriers can achieve uniform loading of active components, thereby improving catalytic efficiency. Commonly used carriers include γ-Al2O3, Co3O4, ZrO2 and TiO2. For example: Patent 202310973243.2 Vacuum-coated integral VOCs precious metal reduction catalyst and preparation method thereof discloses that Pt and Pd are used as precursors, γ-Al2O3 and light rare earth oxides are used as carrier coatings to prepare coated integral VOCs catalysts. Patent 202310518731.4 discloses a catalyst for catalytic combustion and degradation of CVOCs, its preparation method and application, which loads CeO2 on SiO2, Al2O3 and zeolite carrier materials, all of which show good low-temperature catalytic activity of 1,2-dichlorobenzene. Patent 202210827387.2 discloses a method for loading Ru on CeO2, Y2O3, In2O3, and Al2O3 carriers, and the active components of this type of catalyst show strong binding ability with the carrier in promoting the catalytic dehydrogenation process of ammonium lactate. The current technology shows that the catalyst carrier has a significant effect on the catalytic activity of precious metal active components such as Pt and Pd. However, conventional carrier materials such as γ-Al2O3, Co3O4, and ZrO2 are prone to sintering, agglomeration, and loss under high-temperature catalytic conditions, and can even generate inert composite metal oxides with non-precious metal active components, which greatly limits the industrial application of non-precious metal materials. Summary of the invention

[0005] The purpose of the present invention is to provide a high thermal conductivity composite perovskite catalyst and a preparation method thereof. By adopting a high thermal conductivity material as a carrier and introducing a metal additive, the high temperature catalytic stability, aging resistance and carbon deposition performance of the catalyst are improved, high temperature agglomeration is inhibited, and the catalytic performance is improved.

[0006] To achieve the above-mentioned object, the present invention provides a high thermal conductivity composite perovskite catalyst, the general chemical formula of which is MFC / MN, wherein MFC is the catalytic active center perovskite with a mass fraction of 60wt.% to 80wt.%; M is a catalyst carrier, and BN high thermal conductivity carrier is selected, accounting for 9wt.% to 30wt.% of the mass percentage of the catalyst; N is a metal additive La, which accounts for 1wt.% to 30wt.% of the mass percentage of the catalyst.

[0007] Preferably, the MFC is LaMn 0.8 Fe 0.15 Co 0.05 O3 perovskite, M is BN, and N is La.

[0008] The method for preparing the above-mentioned high thermal conductivity composite perovskite catalyst comprises the following steps:

[0009] S1. Pre-treat the catalyst carrier M by placing it in an oxalic acid solution at 50°C to 70°C and stirring it, filter the suspension, wash it with deionized water until the pH value is neutral, and place the treated M in a vacuum drying oven for drying to obtain pre-treated M for standby use;

[0010] S2, adding deionized water to the pretreatment M, stirring at room temperature for 30 minutes, and dropping polyethylene glycol; adding a metal salt containing a metal additive to deionized water, treating it in a water bath, and then placing it in a vacuum drying oven for drying to obtain a modified carrier precursor powder;

[0011] S3, placing the modified carrier precursor powder in a muffle furnace for calcination at a temperature of 400° C. to 600° C. for a time of 2 h to 3 h to obtain a modified carrier material MN; the particle size of the modified carrier material MN is 10 μm to 20 μm;

[0012] S4, weighing lanthanum nitrate, manganese nitrate, iron nitrate, cobalt nitrate, and complexing agent raw materials, dissolving the raw materials in deionized water to obtain a mixed solution, stirring at room temperature for 30 minutes, and adding alkaline solution dropwise to the mixed solution under stirring until the pH of the mixed solution is 1.5-3.0;

[0013] S5, placing the mixed solution in a water bath magnetic stirrer, adding hydroxyethyl cellulose under stirring conditions, the water bath temperature is 60°C to 85°C, and continuously stirring to form a sol, adding the modified carrier material MN and polyethylene glycol to the mixed solution, and stirring to form a viscous gel;

[0014] S6, placing the viscous gel in a muffle furnace at 300° C. to 550° C. for the first calcination, the calcination time being 30 min to 60 min, to obtain a catalyst precursor powder;

[0015] S7. Grind the catalyst precursor powder for the first time, and the particle size of the first grinding is 0.5mm~1.5mm; after compaction, place it in a muffle furnace for a second calcination, the second calcination temperature is 700℃~850℃, and the calcination time is 1h~5h; after calcination, cool to room temperature, and grind it for the second time to obtain a high thermal conductivity composite perovskite catalyst MFC / MN with a particle size of 10μm~20μm.

[0016] Preferably, in S1, the concentration of the oxalic acid solution is 0.1 mol / L to 1.0 mol / L, the stirring pretreatment time is 4 h to 5 h, and the drying temperature of the vacuum drying oven is 90° C. to 105° C.

[0017] Preferably, in S2, the amount of polyethylene glycol added is 0.01wt.% to 5.00wt.% of the catalyst; the metal salt is a metal nitrate, metal sulfate, metal acetate or metal chloride containing a metal additive, and the amount of the metal salt added is 1wt.% to 30wt.% of the catalyst.

[0018] Preferably, in S2, the water bath temperature is 60°C to 85°C, the rotary evaporation is 1h to 5h; and the drying temperature of the vacuum drying oven is 90°C to 105°C.

[0019] Preferably, in S4, the molar ratio of the Mn, Fe and Co metals is 14:2:1 to 18:4:1; the complexing agent is a mixture of citric acid and glucose with a molar ratio of 8:2, and the molar ratio of the complexing agent to the total metal ions is 1.5:1 to 2:1; the alkaline solution is a mixture of one or more of ammonia water, sodium hydroxide, potassium hydroxide and sodium carbonate.

[0020] Preferably, in S5, the added amount of hydroxyethyl cellulose is 0.05wt.% to 0.35wt.%; the sol stirring speed is 300r / min to 600r / min, and the stirring is 2h to 3h; the modified carrier material MN accounts for 10wt.% to 60wt.% of the total mass of the overall catalyst, and the added amount of polyethylene glycol is 0.13wt.% to 3wt.%.

[0021] Preferably, the calcination heating rate in S3, S6 and S7 is 1°C / min to 10°C / min, and air or nitrogen is continuously introduced during the calcination process, with a flow rate of 30mL / min to 60mL / min.

[0022] Preferably, the method further comprises a regeneration process of calcining the catalyst in an air atmosphere, wherein the calcination temperature is 400° C. to 600° C. and the calcination time is 20 min to 60 min.

[0023] The advantages and positive effects of the high thermal conductivity composite perovskite catalyst and the preparation method thereof of the present invention are:

[0024] 1. The present invention uses high thermal conductivity hexagonal boron nitride as a carrier. The thermal stability of boron nitride effectively prevents the formation of inert oxides between the active center component and the carrier. At the same time, the thermal conductivity of boron nitride material is close to that of metal, which is conducive to transferring the heat generated by the catalytic reaction from the carrier coating to other parts of the catalyst, further enhancing the overall performance of the catalyst and improving the stability of the catalyst material under high temperature conditions.

[0025] 2. The present invention introduces a metal additive La to form a new MFC / BN-La catalyst. The metal additive increases catalyst defects, inhibits high-temperature sintering and agglomeration, and improves catalytic stability, aging resistance and carbon deposition performance. The synergistic effect between perovskite, carrier material and metal additive, compared with pure perovskite catalyst material, the composite catalyst exhibits better catalytic performance, higher surface ion mobility, more variable oxidation states and structural defects. The substitution of different metal additives can improve the selectivity of the catalyst for characteristic reactions. At the same time, it can further improve its stability in high temperature and complex reaction environments, prevent the sintering and deactivation of the active components of the catalyst, and extend the service life of the catalyst. While improving the stability of the methane thermal storage combustion process, it increases the specific surface area of ​​the material and the exposure of the perovskite active sites to a certain extent. In addition, the introduction of metal additives promotes the reduction and regeneration of the catalyst and improves the reuse rate of the catalyst.

[0026] 3. The catalytic active center of the present invention adopts LaMn 0.8 Fe 0.15 Co 0.05 O3 perovskite, LaMn 0.8 Fe 0.15 Co 0.05 O3 perovskite is loaded on a carrier material with a particle size of 60nm to 100nm. The material shows significant advantages in redox, structural stability, electronic conduction and environmental friendliness.

[0027] 4. The preparation method of the present invention has a simple and easy-to-control process, short heat treatment time, low preparation cost, and is more suitable for industrial production. The activity of the prepared MFC / BN-La catalyst is comparable to that of traditional precious metal catalysts in industrial applications such as low-concentration methane thermal oxidation, hydrogen sulfide selective oxidation, and styrene production, and has a huge advantage in high-temperature stability.

[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of a flow chart of an embodiment of the present invention;

[0030] Figure 2(a) is the XRD pattern of h-BN, MFC / BN, BN-La, and MFC / BN-La catalysts prepared in Example 1 and Example 9, and (b) is a local enlarged view;

[0031] Figure 3 BET curves and pore size distribution diagrams of h-BN, BN-La, MFC / BN-La, and MFC catalysts prepared in Example 1, Example 9, and Comparative Example 1;

[0032] Figure 4 The scanning electron microscope and energy spectrum analysis diagrams of Examples 1 and 9, (a) is the SEM diagram of Example 1, (b) is the SEM diagram and a local magnified diagram of Example 9, (c) is the distribution diagram of La, Mn, Fe and Co elements in Example 9, and (d) is the distribution diagram of Mn elements in Example 9;

[0033] Figure 5 The methane catalytic combustion performance of the catalyst finally obtained in Examples 1-4 and Comparative Example 1;

[0034] Figure 6 The methane catalytic combustion performance of the catalyst finally obtained in Examples 5-9;

[0035] Figure 7 The MFC / BN-La catalyst obtained in Example 9 was tested 50 times in the range of 250°C to 500°C.

[0036] Figure 8 The MFC / BN-La catalyst obtained in Example 9 was heated at a space velocity of 20000 mL·h -1 ·g cat -1 , catalytic stability at 450℃ and 800℃ for 28h at normal pressure;

[0037] Fig. 9 Carbon deposition analysis of the fresh MFC / BN-La catalyst obtained in Example 9, after aging at 450°C and 800°C;

[0038] Fig.10 The methane catalytic efficiency of the MFC / BN-La catalyst obtained in Example 9 after regeneration. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0040] Figure 1 Schematic diagram of a flow chart of an embodiment of the present invention.

[0041] Example 1

[0042] A method for preparing a high thermal conductivity composite perovskite catalyst comprises the following steps:

[0043] Place 20g of hexagonal boron nitride catalyst carrier in 65℃ oxalic acid solution and stir for 4h. The concentration of oxalic acid solution is 1.0mol / L. Filter the suspension and wash with deionized water until the pH value is neutral. Place the treated h-BN in a vacuum drying oven at 105℃ to dry to obtain pretreated h-BN for later use.

[0044] Weigh 14.724 g of lanthanum nitrate, 9.735 g of manganese nitrate (mass fraction 50%), 2.092 g of ferric nitrate, 0.495 g of cobalt nitrate, 4.640 g of glucose and 21.542 g of citric acid and dissolve them in deionized water to prepare a mixed solution. Stir at room temperature for 30 min, and add ammonia water dropwise to the mixed solution while stirring until the pH of the mixed solution is 1.5.

[0045] The mixed solution was placed in a water bath magnetic stirrer, and 0.295 g of hydroxyethyl cellulose was added under stirring conditions. The water bath temperature was 80°C, and stirring was continued for 3 hours to form a sol state at a stirring speed of 500 r / min. 8.234 g of modified carrier material h-BN and 0.532 g of polyethylene glycol were added to the mixed solution and stirred into a viscous gel.

[0046] The viscous gel was placed in a muffle furnace at 380° C. for the first calcination, and the calcination time was 30 min to obtain a catalyst precursor powder.

[0047] The catalyst precursor powder was coarsely ground and compacted, and then placed in a muffle furnace at 750°C for a second calcination for 2 hours. After calcination, it was cooled to room temperature and finely ground to obtain a high thermal conductivity composite perovskite catalyst MFC / BN.

[0048] Example 2

[0049] This example adopts the method of Example 1 to prepare a high thermal conductivity composite perovskite catalyst MFC / SiC, the only difference being that the carrier material is SiC, wherein the added amount of SiC is 8.234 g.

[0050] Example 3

[0051] This embodiment adopts the method of embodiment 1 to prepare the high thermal conductivity composite perovskite catalyst MFC / Al2O3, the only difference is that the carrier material is Al2O3, wherein the addition amount of Al2O3 is 8.234g.

[0052] Example 4

[0053] This example adopts the method of Example 1 to prepare a high thermal conductivity composite perovskite catalyst MFC / SiO2, the only difference being that the carrier material is SiO2, wherein the added amount of SiO2 is 8.234 g.

[0054] Example 5

[0055] This example is to load a metal additive on the h-BN prepared in Example 1.

[0056] 20g of pretreated h-BN was added to deionized water, stirred at room temperature for 30min, and 0.7g of polyethylene glycol was slowly added; then 10.765g of copper nitrate was added, the water bath temperature was raised to 70°C, and rotary evaporated for 4h; then placed in a 105°C vacuum drying oven for drying. After drying, the powder was placed in a muffle furnace in a nitrogen atmosphere and calcined at 500°C for 2h to obtain a modified BN material, recorded as BN-Cu. On this basis, a high thermal conductivity composite perovskite catalyst MFC / BN-Cu was prepared by the method of Example 1.

[0057] Example 6

[0058] The difference between this embodiment and embodiment 5 is that the metal salt in this embodiment is aluminum nitrate, and the amount of aluminum nitrate added is 13.114 g. A high thermal conductivity composite perovskite catalyst MFC / BN-Al is obtained.

[0059] Example 7

[0060] The difference between this embodiment and embodiment 5 is that the metal salt in this embodiment is zirconium nitrate, and the amount of zirconium nitrate added is 12.419 g. A high thermal conductivity composite perovskite catalyst MFC / BN-Zr is obtained.

[0061] Example 8

[0062] The difference between this embodiment and embodiment 5 is that the metal salt in this embodiment is cerium nitrate, and the amount of cerium nitrate added is 8.908 g. A high thermal conductivity composite perovskite catalyst MFC / BN-Ce is obtained.

[0063] Example 9

[0064] The difference between this embodiment and embodiment 5 is that the metal salt in this embodiment is lanthanum nitrate, and the amount of lanthanum nitrate added is 4.691 g. A high thermal conductivity composite perovskite catalyst MFC / BN-La is obtained.

[0065] Comparative Example 1

[0066] This comparative example is an MFC perovskite catalyst prepared by the method described in Example 1, and no carrier material and metal additive are added to the MFC perovskite catalyst.

[0067] Figure 2(a) is the XRD diagram of h-BN, MFC / BN, BN-La, and MFC / BN-La catalysts prepared in Example 1 and Example 9, and (b) is a local enlarged view. BN-La and MFC / BN-La catalysts are represented by Example 1 and Example 9, respectively. As can be seen from Figure (a), both Examples 1 and 9 have h-BN characteristic diffraction peaks belonging to the hexagonal crystal structure at positions such as 26.7°, 41.7°, 50.2°, and 54.9°. Unlike BN and BN-La, Example 1 has LaMnO with a rhombohedral symmetrical crystal structure at 32.5°, 40.3°, 47.0°, and 58.4°. 3.26 The perovskite phase diffraction peak proves the high loading of perovskite on BN. Moreover, with the addition of additive La, the height of the perovskite diffraction peak is further reduced. This phenomenon shows that the additive La can help improve the uniformity of the dispersion of active centers on the BN carrier. Figure 2 (b) It can be seen that with the addition of the auxiliary agent La and the loading of the active center MFC, the half-peak width and diffraction intensity of the main diffraction peak (2θ=26.7°) both decrease, indicating changes in the crystallinity and grain diameter of the BN material.

[0068] Figure 3 The BET curves and pore size distribution diagrams of the h-BN, BN-La, MFC / BN-La, and MFC catalysts prepared in Example 1, Example 9, and Comparative Example 1 are shown. Figure 3 It can be clearly seen that the perovskites all show a type IV isotherm with an H1 hysteresis loop, which means that the perovskite catalyst has a typical mesoporous structure. The hysteresis loops formed at a lower relative pressure in Comparative Example 1 and Example 9 confirm that their BET specific surface areas are larger than those of the other two catalysts. The specific surface area, total pore volume and average pore diameter parameters of Comparative Example 1 and Example 9 are shown in Table 1. Among them, the total pore volume (0.07 cm 3 / g) and the average pore size (11.2nm) are the largest. With the loading of MFC perovskite on the BN-La carrier, the total pore volume and the average pore size decrease to a certain extent, which is related to the coverage of some mesopores in MFC by BN and La2O3. However, the specific surface area of ​​Example 9 is 28.8m 2 / g, which is significantly higher than that of Comparative Example 1, indicating that the surface of Example 9 has more porous structures and better dispersibility. The larger specific surface area provides more active reaction sites for the catalytic reaction, which can promote the adsorption and migration of CH4 and O2 on the surface of the perovskite catalyst, thereby improving the catalytic efficiency of the perovskite.

[0069] Table 1 Pore structure parameters of MFC and MFC / BN-La catalysts prepared in Comparative Example 1 and Example 9

[0070]

[0071] Figure 4 The scanning electron microscope and energy spectrum analysis diagrams of Examples 1 and 9, (a) is the SEM diagram of Example 1, (b) is the SEM diagram and partial magnification diagram of Example 9, (c) is the distribution diagram of La, Mn, Fe and Co elements in Example 9, and (d) is the distribution diagram of Mn elements in Example 9. Figure 4 As can be seen in (a), a three-dimensional, porous MFC structure appears on the surface of the boron nitride carrier. With the aid of the additive La, the MFC morphology becomes more fluffy and the number of mesopores increases, forming a non-uniform porous structure. At the same time, the number of MFC particles in the field of view increases, indicating that the perovskite particles are more delicate and dense, which is conducive to the efficient loading of MFC on the unit BN carrier. Figure 4 (b) shows that after the introduction of the metal additive La, the originally smooth surface of the material becomes rough, and some disordered nano-La2O3 particles accumulate on the BN surface to form a heterogeneous structure similar to nanoclusters. Figure 4 The good overlap of La, Mn, Fe and Co in (c) indicates the presence of MFC perovskite in the catalyst. Figure 4 (d) shows that the Mn element is mainly concentrated in the left half of the picture. The quantitative results of the elemental composition of MFC and MFC / BN-La catalysts in Comparative Example 1 and Example 9 were obtained by EDS-mapping, as shown in Table 2 below. In Comparative Example 1, the Mn content reached 13.94%, the La content was 14.87%, and the O content exceeded 60%. O / La was higher than LaMnO3, proving the superstoichiometric oxygen perovskite crystal structure of MFC. This structure is continued in Example 9. The O / La in the catalyst of Example 9 is as high as 5.35. Considering the high stability of BN, this part of the O element comes from the MFC perovskite, and the rest is attributed to the introduction of the La2O3 additive or the adsorption of oxygen on the surface of the porous catalyst.

[0072] Table 2 Surface component structures of MFC and MFC / BN-La catalysts in Comparative Example 1 and Example 9

[0073]

[0074] Figure 5 The methane catalytic combustion performance of the catalysts finally obtained in Examples 1-4 and Comparative Example 1 is as follows: Figure 6 The methane catalytic combustion performance of the catalyst finally obtained in Examples 5-9 is shown in FIG. Figure 5 , 6 The ignition temperature (T 10 ) and complete combustion temperature (T 90) value is the lowest, and the catalyst can completely oxidize methane at a temperature below 470°C, and the overall catalytic temperature value is significantly lower than other controls. The catalyst activity can be improved to a certain extent by increasing the thermal conductivity of the carrier. Example 1 has the highest catalytic oxidation efficiency for methane. This is because the excellent thermal conductivity of the BN carrier is conducive to transferring the heat generated by the exothermic reaction from the reaction site to other parts of the catalyst, thereby improving the overall catalytic efficiency of the perovskite. On this basis, the catalytic performance is further improved by the introduction of different metal additives Cu, Al, Ce, Zr and La. Among them, the catalytic efficiency of Example 9 at 450°C increased to 86.8%. Compared with Cu, Al, Ce, and Zr metals, the additive La has the most obvious promoting effect on the catalytic activity of MFC / BN.

[0075] Figure 7 The MFC / BN-La catalyst obtained in Example 9 was tested 50 times in the range of 250°C to 500°C. Figure 7 As shown, there was no significant decrease in the methane catalytic performance of the catalyst before and after the cycle test. Figure 8 The MFC / BN-La catalyst obtained in Example 9 was heated at a space velocity of 20000 mL·h -1 ·g cat -1 , catalytic stability at 450℃ and 800℃ for 28h at normal pressure. Figure 8 As shown, under the conventional 450°C condition, the methane conversion rate of Example 9 is maintained at 82.1%, which shows the reliability of the catalyst prepared by the present invention under conventional conditions. At a temperature of 800°C, the methane conversion rate of the catalyst in the first 21 hours is maintained at 100%, and gradually decreases as the reaction proceeds. After 25 hours of continuous reaction, the methane conversion rate only decreases by 2.6%. Considering that extreme conditions are not common, Example 9 has a relatively ideal high-temperature operation reliability. The above results prove that the modification method of the present invention with high thermal conductivity carrier loading and coordinated metal auxiliary modification is a very promising method to improve catalytic activity and high-temperature stability.

[0076] Fig. 9 Carbon deposition analysis of the fresh MFC / BN-La catalyst obtained in Example 9, after aging at 450°C, and after aging at 800°C. Fig. 9As shown, the weight loss in the first stage is between 80°C and 300°C, which is related to the adsorption of water vapor by the catalyst. The weight loss in the second stage occurs in the temperature range of 300°C to 700°C, which is due to the removal of carbon substances deposited on the catalyst surface and the slight decomposition of inorganic compounds. As the temperature continues to rise (>700°C), the weight loss is mainly attributed to the enhanced activity and mobility of oxygen species under high temperature conditions. Therefore, the weight loss rates of Example 9 in the second stage after constant temperature aging at 450°C and 800°C are 0.29% and 0.35%, respectively, which are greater than those of fresh samples, indicating that the catalyst has different degrees of carbon deposition after long-term high temperature testing, and the carbon deposition phenomenon of Example 9 aged at 800°C is relatively serious due to the higher reaction temperature. If the water vapor and carbon deposition adsorbed on the catalyst surface are removed by regeneration technology, the service life of the catalyst will inevitably be increased and the operating cost will be reduced.

[0077] The MFC / BN-La catalyst was calcined at 500°C in an air atmosphere for 30 minutes for regeneration to remove carbon deposited on the catalyst surface. Fig.10 The methane catalytic efficiency after the regeneration of the MFC / BN-La catalyst obtained in Example 9. Fig.10 As shown in the figure, after 25h of methane catalytic combustion, the conversion rate of the MFC / BN-La catalyst at 450℃ was only 82.1%. After regeneration, this parameter increased to 83.9%, which is equivalent to the activity of the fresh sample. This is because some active sites of the catalyst are re-exposed after carbon removal. The catalytic activity of the regenerated MFC / BN-La catalyst increased by 1.1% at 800℃. The methane catalytic efficiency of the MFC / BN-La catalyst after regeneration was maintained above 98%, which shows that the catalyst has good stability and reusability.

[0078] Therefore, by using the high thermal conductivity composite perovskite catalyst and its preparation method described in the present invention, by using a high thermal conductivity material as a carrier and introducing a metal additive, the high-temperature catalytic stability, aging resistance and carbon deposition performance of the catalyst are improved, high-temperature agglomeration is inhibited, and the catalytic performance is improved.

[0079] Finally, it should be noted that: in the above description, many specific details are described in order to fully understand the present invention, but the above description is only a preferred embodiment of the present invention. The present invention can be implemented in many other ways different from those described herein, so the present invention is not limited to the specific implementation disclosed above. At the same time, any person familiar with the technical field can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.

Claims

1. A high thermal conductivity composite perovskite catalyst, characterized in that: The general chemical formula is MFC / MN, wherein MFC is the catalytically active center perovskite, M is the catalyst carrier, and N is the metal additive. The mass percentage of the catalyst carrier M to the catalyst is 9wt.% to 30wt.%, the mass percentage of the metal additive N to the catalyst is 1wt.% to 30wt.%, and the mass percentage of the catalyst active center perovskite to the catalyst is 60wt.% to 80wt.%.

2. A high thermal conductivity composite perovskite catalyst according to claim 1, characterized in that: The MFC is LaMn 0.8 Fe 0.15 Co 0.05 O3 perovskite, M is BN, and N is La.

3. The method for preparing a high thermal conductivity composite perovskite catalyst according to claim 2, characterized in that: The following steps are involved: S1. Pre-treat the catalyst carrier M by placing it in an oxalic acid solution at 50°C to 70°C and stirring it, filter the suspension, wash it with deionized water until the pH value is neutral, and place the treated M in a vacuum drying oven for drying to obtain pre-treated M for standby use; S2, adding deionized water to the pretreatment M, stirring at room temperature for 30 minutes, and dropping polyethylene glycol; adding a metal salt containing a metal additive to deionized water, treating it in a water bath, and then placing it in a vacuum drying oven for drying to obtain a modified carrier precursor powder; S3, placing the modified carrier precursor powder in a muffle furnace for calcination at a temperature of 400° C. to 600° C. for a time of 2 h to 3 h to obtain a modified carrier material MN; the particle size of the modified carrier material MN is 10 μm to 20 μm; S4, weighing lanthanum nitrate, manganese nitrate, iron nitrate, cobalt nitrate, and complexing agent raw materials, dissolving the raw materials in deionized water to obtain a mixed solution, stirring at room temperature for 30 minutes, and adding alkaline solution dropwise to the mixed solution under stirring until the pH of the mixed solution is 1.5-3.0; S5, placing the mixed solution in a water bath magnetic stirrer, adding hydroxyethyl cellulose under stirring conditions, the water bath temperature is 60°C to 85°C, and continuously stirring to form a sol, adding the modified carrier material MN and polyethylene glycol to the mixed solution, and stirring to form a viscous gel; S6, placing the viscous gel in a muffle furnace at 300° C. to 550° C. for the first calcination, the calcination time being 30 min to 60 min, to obtain a catalyst precursor powder; S7. Grind the catalyst precursor powder for the first time, and the particle size of the first grinding is 0.5mm~1.5mm; after compaction, place it in a muffle furnace for a second calcination, the second calcination temperature is 700℃~850℃, and the calcination time is 1h~5h; after calcination, cool to room temperature, and grind it for the second time to obtain a high thermal conductivity composite perovskite catalyst MFC / MN with a particle size of 10μm~20μm.

4. The method for preparing a high thermal conductivity composite perovskite catalyst according to claim 3, characterized in that: In the S1, the concentration of the oxalic acid solution is 0.1 mol / L to 1.0 mol / L, the stirring pretreatment time is 4 h to 5 h, and the drying temperature of the vacuum drying oven is 90° C. to 105° C.

5. The method for preparing a high thermal conductivity composite perovskite catalyst according to claim 3, characterized in that: In S2, the amount of polyethylene glycol added is 0.01wt.% to 5.00wt.% of the catalyst; the metal salt is a metal nitrate, metal sulfate, metal acetate or metal chloride containing a metal additive, and the amount of the metal salt added is 1wt.% to 30wt.% of the catalyst.

6. The method for preparing a high thermal conductivity composite perovskite catalyst according to claim 3, characterized in that: In S2, the water bath temperature is 60°C to 85°C, and the rotary evaporation is performed for 1h to 5h; the drying temperature of the vacuum drying oven is 90°C to 105°C.

7. The method for preparing a high thermal conductivity composite perovskite catalyst according to claim 3, characterized in that: In the S4, the molar ratio of the Mn, Fe and Co metals is 14:2:1 to 18:4:1; the complexing agent is a mixture of citric acid and glucose with a molar ratio of 8:2, and the molar ratio of the complexing agent to the total metal ions is 1.5:1 to 2:1; the alkaline solution is a mixture of one or more of ammonia water, sodium hydroxide, potassium hydroxide and sodium carbonate.

8. The method for preparing a high thermal conductivity composite perovskite catalyst according to claim 3, characterized in that: In the S5, the addition amount of hydroxyethyl cellulose is 0.05wt.% to 0.35wt.%; the sol stirring speed is 300r / min to 600r / min, and the stirring is 2h to 3h; the modified carrier material MN accounts for 10wt.% to 60wt.% of the total mass of the whole catalyst, and the addition amount of polyethylene glycol is 0.13wt.% to 3wt.%.

9. The method for preparing a high thermal conductivity composite perovskite catalyst according to claim 3, characterized in that: The calcination heating rate in S3, S6 and S7 is 1°C / min to 10°C / min, and air or nitrogen is continuously introduced during the calcination process, with a flow rate of 30mL / min to 60mL / min.

10. The method for preparing a high thermal conductivity composite perovskite catalyst according to claim 3, characterized in that: The method also includes a regeneration process of calcining the catalyst in an air atmosphere, wherein the calcination temperature is 400° C. to 600° C. and the calcination time is 20 minutes to 60 minutes.

Citation Information

Patent Citations

  • Ruthenium-loaded metal oxide catalyst as well as preparation method and application thereof

    CN115121248A

  • Catalyst for catalytic combustion degradation of CVOCs and preparation method and application thereof

    CN116212932A

  • Vacuum coating type integral precious metal reduction catalyst for VOCs and preparation method of vacuum coating type integral precious metal reduction catalyst

    CN116673025A